2013
DOI: 10.1155/2013/941237
|View full text |Cite
|
Sign up to set email alerts
|

Role of the Endocannabinoid System in the Central Regulation of Nonmammalian Vertebrate Reproduction

Abstract: The endocannabinoid system (ECS) has a well-documented pivotal role in the control of mammalian reproductive functions, by acting at multiple levels, that is, central (CNS) and local (gonads) levels. Since studies performed in animal models other than mammals might provide further insight into the biology of these signalling molecules, in the present paper we review the comparative data pointing toward the endocannabinoid involvement in the reproductive control of non-mammalian vertebrates, focussing in partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 63 publications
0
7
0
Order By: Relevance
“…Based on several studies that have reported the implication of the ECS in reproductive processes in a number of animals (Cottone et al, 2013(Cottone et al, , 2008, and with the levels of sex-steroids (Gorzalka and Dang, 2012;Maccarrone et al, 2000;Rossi et al, 2007), the present study examined the effects of a novel plasticizer, the DiNP, on the male gilthead seabream ECS and reproductive function.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on several studies that have reported the implication of the ECS in reproductive processes in a number of animals (Cottone et al, 2013(Cottone et al, , 2008, and with the levels of sex-steroids (Gorzalka and Dang, 2012;Maccarrone et al, 2000;Rossi et al, 2007), the present study examined the effects of a novel plasticizer, the DiNP, on the male gilthead seabream ECS and reproductive function.…”
Section: Discussionmentioning
confidence: 99%
“…In this context, the ECS is a lipid-based signaling system involved in the regulation of a plethora of physiological functions, including reproduction in both mammalian and non-mammalian species (Maccarrone, 2009;Meccariello et al, 2014). Among bony fish, the ECS has been described in the gonads of Danio rerio (Forner-Piquer et al, 2018b), Sparus aurata (Ruggeri et al, 2007) and Carassius auratus (Cottone et al, 2013), among other species. As me mentioned above, the ECS plays a key signal in the control of reproduction.…”
Section: Graphical Abstract Introductionmentioning
confidence: 99%
“…In mammalian and non-mammalian vertebrates, the endocannabinoid system regulates hypothalamic GnRH neurons and pituitary LH cells directly and indirectly [see reviews in Ref. ( 281 , 282 )]. Interrelation among these systems might be an additional mechanism underlying the interaction between mood, stress, appetite, and reproduction.…”
Section: Perspectivesmentioning
confidence: 99%
“…On the other hand, the implication of the Endocannabinoid System (ECS) in both mammalian and non-mammalian species reproductive events is also well documented, being a lipid signaling system pivotal for the success of reproductive performance and closely related to the levels of sexsteroids [21]. The ECS is present in the gonads of teleosts, among other tissues, as it has been previously reported in zebrafish Danio rerio [22], goldfish Carassius auratus [23] and gilthead sea bream Sparus aurata [24], with a functional relevance in teleost reproduction [23,25]. Local mediators, namely the endocannabinoids (Anandamide (AEA) and 2-arachidonoylglycerol (2-AG)), their membrane receptors (endocannabinoid receptor type I (CNR1) and type II (CNR2), vanilloid receptor (TRPV1)) and the enzymatic machinery that regulates the levels of the endocannabinoids, compose the ECS, as thoroughly described in several review articles [26][27][28].…”
Section: Introductionmentioning
confidence: 91%